1994
DOI: 10.2466/pr0.1994.74.1.311
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Dream Perspectives

Abstract: A study exploring gender differences in self-reported dream perspectives was performed with 282 college students. Significantly more of the 164 women reported dreaming exclusively in first person and more of the 114 men exclusively in third person. Also, gender differences were found for those who dreamed in mixed perspective, a combination of first- and third-person points of view. Possible reasons for these differences were suggested and further research posited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The neutron experiments have been performed on SANDALS diffractometer at the ISIS spallation neutron source, located at the Rutherford Appleton Laboratory (United Kingdom). The neutron data have been corrected for detectors efficiency, attenuation, multiple scattering, and inelastic scattering using well established methods . White beam X‐ray diffraction data have been collected on a Panaytical Ag‐source diffractometer also available at ISIS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutron experiments have been performed on SANDALS diffractometer at the ISIS spallation neutron source, located at the Rutherford Appleton Laboratory (United Kingdom). The neutron data have been corrected for detectors efficiency, attenuation, multiple scattering, and inelastic scattering using well established methods . White beam X‐ray diffraction data have been collected on a Panaytical Ag‐source diffractometer also available at ISIS.…”
Section: Methodsmentioning
confidence: 99%
“…High‐energy X‐ray data were corrected for detector efficiency, polarisation, Compton scattering and fluorescence . Computational models of the system have been obtained through Empirical Potential Structure Refinement (EPSR) and implemented with EPSRgui . The simulation boxes contain 20 solute and 1100 solvent molecules, at the density of 0.1 atoms/Å 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Investigators who have worked with the manifest content of reported dreams have also studied groups within cultures. Gender differences, for example, have emerged whenever male and female dream reports have been compared (e.g., Domhoff, 1996;Nielsen et al, 2003;Soper, Rosenthal, & Milford, 1994). Therefore, this study asked the question, "Are there significant content differences between male and female dream reports obtained in dream seminars conducted in England?…”
Section: Introductionmentioning
confidence: 98%
“…In 1966, Hall and Van de Castle published The Content Analysis of Dreams, which outlines a thorough coding system with which they investigated 1,000 dreams collected from 200 undergraduates from Case Western Reserve University and Baldwin Wallace College in Cleveland, Ohio, between 1947 and1952. Since that time, the Hall-Van de Castle system has been used to compare groups of various ages, cultural backgrounds, and diagnostic categories, as well as genders (e.g., Coté, Lortie-Lussier, Roy, & De Koninck, 1996;Kane, Mellen, Patten, & Samano, 1993;Krippner, Lenz, Barksdale, & Davidson, 1974;Krippner, Posner, Pomerance, Barksdale, & Fischer, 1974;Krippner, Winkler, Rochlen, & Yashar 1998;Lortie-Lussier, Schwab, & De Koninck, 1985;Rubinstein & Krippner, 1991;Soper, Rosenthal, & Milford, 1994). Reliability, by the method of common agreement, ranges from .60 to .90 for the various categories, a range suitable for most research studies; Van de Castle (1969) has addressed validity concerns.…”
mentioning
confidence: 99%